The activities of the lower circuit of the urban economy and the factors of Attraction and Dispersion of Downtown and Newton Pereira Gonçalves of the city of União dos Palmares / AL / As atividades do circuito inferior da economia urbana e os fatores de atração e dispersão do centro e no bairro Newton Pereira Gonçalves da cidade de União dos Palmares/AL - Reynaldo Daivyd Lopes da Silva; Amistson Lopes da Silva (Universidade Estadual de Alagoas, 2017)
In the period in which technical systems present themselves as protagonists of the space organization process, the activity of the lower circuit of the urban economy is presented as an important element to understand the relationship of the urban system. The main purpose of this article is to study the factors of attraction and dispersion of the lower circuit activities in the center of Union of Palmares / AL and in the neighborhood Newton Pereira Goncalves created by the removal of dozens of families who lived the banks of Mundaú river and were hit by a natural disaster, a flood occurred in 2010. As theoretical support, we SANTOS works (2008), Correa (1995) and Silveira (2010). Data collection was structured questionnaire applications, and informal conversations with the lower circuit of the agents of central and Newton Pereira neighborhood held with field activity, essential for the research in question. The results show that factors of attraction and repulsion factors are directly linked to permanence or adaptation of a particular activity where these agents are attracted by the emergence of the needs of the population. Finally, the increase in inequality of territorial configuration, force individuals to seek alternatives to survive, face at the same time the existence of economic barriers or advantages that can attract or disperse the activities of the lower circuit by urban sprawl.